Free thinking for expressivists - Sinclair, Neil (2008)
This paper replies to Zangwill’s argument that quasi-realists cannot accommodate the conceptual status of claims of moral mind-independence embedded in ordinary moral thought. I argue that this conceptual status is compatible with an ‘internal reading’ of such claims once one recognises the essential co-ordinating role of moral judgement. I also argue that an ‘external reading’ is available for an ‘essentialist’ type of mind-independence claim recently identified by Jenkins.